Comparative study of performance of temiki (Melastomacandidum) and rubek (Calotropis gigantea) extract inhibitors for carbon steel in corrosive media - Supardi, Joli; Rizal, Samsul; Ali, Nurdin; Fonna, Syarizal; Ikramullah, Ikramullah; Veranita, Veranita; Arifin, A.K. (Jurnal Polimesin, 2023)
The use of synthetic inhibitors that negatively affect the environment is still used. Organic inhibitors are the best and most environmentally friendly solutions such as Temiki plants (MelastomaCandidum) and Rubik (Calotropis Giganteen) which have good corrosion cell inhibitor properties and have the potential to be used as corrosion inhibitors. This study analyzed Temiki and Rubik extracts as corrosion inhibitors in carbon steel using the weight loss method in 3.5% NaCl solution and analyzed the efficiency of the inhibitors. Temiki and Rubik's are extracted by drying the leaves, stems and flowers under the sun. Then the material is mashed together and distilled by the solid-liquid method with the Soxhlet tool. Identification of plant components using Gas Chromatography-Mass Spectrometry (GC-MS). Density and viscosity were analyzed following ASTM D 4052 and ASTM D 445 standards. Weight loss method testing was carried out at inhibitor concentrations of 200, 300, 400 and 500 ppm, with soaking time for 15 weeks and data collection was carried out every week. The results of the analysis showed the highest corrosion rate in Temiki extract with a concentration of 500 ppm reaching 1,569 mpy and the lowest at a concentration of 500 ppm reaching 0.157 mpy. In Rubik's extract inhibitors, the highest corrosion rate occurred in 500 ppm inhibitors reaching 1,268 mpy, while the lowest occurred at 200 ppm concentrations reaching 0.331 mpy. The highest efficiency value is the 400 ppm Temiki inhibitor with efficiency reaching 82.89% and the lowest at 500 ppm reaching 19.55%. while for the efficiency of Rubik's extract inhibitors, the highest value was 62.71%, at a concentration of 200 ppm. While the lowest is 28.40%, at 500 ppm inhibitors. These results show that Temiki and Rubik's extracts can still function well as corrosion inhibitors in low-carbon steels in NaCl solution.